Indonesia's Interest in The South-South Triangular Cooperation (SSTC) Policy to Fiji during Joko Widodo’s 2014-2019 Government - Ica Cahayani (Global South Review, 2021)
This study was conducted to explain Indonesia's interests in the South-South Triangular Cooperation (SSTC) policy towards Fiji in the Joko Widodo administration in 2014-2019. This study uses the theory of national interest and foreign policy. The research method used is descriptive qualitative. The research method is used to explain and explore Indonesia's interests through the SSTC's policy towards Fiji with three interests, namely economic, political and security interests. The results showed that Indonesia chose Fiji as a country to implement the SSTC policy because Fiji is one of the south Pacific countries, especially Melanesian countries and Indonesia still failed to carry out diplomacy with Vanuatu. Fiji is a country that has an important role in the internal organization of the Melanesian Spearhead Group (MSG), Fiji's involvement is very large in making MSG policies, because Indonesia's goal of being included in the MSG requires a major country that has an important role in the MSG, Besides Indonesia having economic interests, Fiji provides opportunities big for economic development and new market share for Indonesia in the south Pacific region, considering that this region is very strategic, this region has become the location of a trade war between China and the United States. Indonesia's strategy to gain economic, political and security interests by providing through the implementation of the SSTC policy is a form of great concern for Fiji.